Preparation method of MOFs (Metal-Organic Frameworks) mixed matrix membrane for carbon capture defects

By introducing defective structures into MOFs, using metal ions and hydroxyl coordination and functional small molecule β-cyclodextrin regulation, the problem of difficult to prepare membrane materials with high permeability and high selectivity in the prior art is solved, and efficient gas separation and CO2 adsorption performance are achieved.

CN119680400AActive Publication Date: 2025-03-25DALIAN UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510024541.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-03-25
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

The prior art is difficult to prepare membrane materials with high permeability and high selectivity through a short reaction process, especially in the field of carbon capture, where defective MOFs materials cannot simultaneously improve gas separation performance and interface compatibility.

Method used

Through the mechanism of mutual coordination between metal ions and hydroxyl groups, the functional small molecule β-cyclodextrin is used as a regulator to introduce defective structures into MOFs, adjust the pore structure and improve the gas transmission channel, while exposing metal sites to enhance CO2 adsorption performance.

Benefits of technology

A membrane material with both high permeability and high selectivity is achieved, which improves gas separation performance and CO2 adsorption capacity, and improves the interface compatibility between polymer matrix and MOFs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680400A_ABST
    Figure CN119680400A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an MOFs (Metal Organic Frameworks) mixed matrix membrane for carbon capture defects, which adopts an in-situ synthesis strategy, utilizes the principle that metal ions can coordinate with hydroxyl to form a complex, takes functional micromolecule beta-cyclodextrin rich in hydroxyl as a regulator, and occupies original binding sites by coordinating with the metal ions to form the MOFs mixed matrix membrane. A defect structure is introduced into MOFs in a competitive coordination mode. Due to the introduction of the defect structure, on one hand, the pore structure of the MOFs is adjusted, and on the other hand, the hollow cylindrical structure of the functional small molecules provides an additional channel for gas transmission, so that the permeability and the gas screening capacity are further improved; on the other hand, the metal sites are exposed, and interaction exists between the metal sites and CO2; hydrogen bond interaction exists between exposed carboxyl and the polymer, so that the interfacial compatibility is improved; in addition, hydroxyl and CO2 have good affinity, and the material with high permeability and high selectivity is obtained under multiple action coupling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of gas membrane separation and relates to a method for preparing a defective MOFs mixed matrix membrane for carbon capture. Background Art

[0002] CO2 capture, utilization and storage technology is a hot topic in current society. On the one hand, CO2 is the main cause of the greenhouse effect. On the other hand, as an extremely important industrial raw material, CO2 storage and transportation is also an extremely important issue. Traditional CO2 separation methods include low-temperature separation, pressure swing adsorption, chemical absorption and other methods. Gas membrane separation technology is widely used due to its simple operation, stable and sustainable operation. In membrane separation technology, polymer membranes are limited by their "Trade-Off" phenomenon; although inorganic membranes have excellent performance, their high price and fragility limit their industrial development; mixed matrix membranes (MMMs) are prepared by blending polymer matrix and inorganic fillers. It combines the advantages of polymer membranes and inorganic membranes, greatly improving the gas separation performance of the membrane.

[0003] The selection of inorganic fillers is a key factor in improving the performance of mixed matrix membranes. Among many inorganic fillers, metal organic frameworks (MOFs) are widely used in gas separation, catalysis, medicine and other fields due to their high specific surface area, high porosity and regular and adjustable pore size. The gas separation performance of mixed matrix membranes can be effectively improved by selecting specific MOFs and modifying them. Some researchers have modified MOFs by chemical etching, heat treatment and other methods to create hierarchical pores in MOFs, which helps to improve the diffusion rate of gases. However, this method has poor reproducibility and has certain requirements for the structure of MOFs itself. A one-step method can also be used to select suitable metal clusters and ligands to prepare MOFs materials that meet the expected standards, but this method has some restrictions on the types of ligands and metal clusters and is difficult to apply on a large scale; post-modification to introduce small molecules to adjust the pore structure is also a common method, but this method will sacrifice some permeability while improving selectivity, because the introduction of small molecules will reduce the pore size. Therefore, how to prepare membrane materials with both high permeability and high selectivity through a shorter reaction process has become the current research goal. Defect engineering is an emerging method to regulate the structure of MOFs. Compared with perfect MOFs crystals, defective MOFs will show superior performance in applications, thanks to the enhancement of porosity and the generation of abundant active sites. Zhong Chongli and others from Tianjin Polytechnic University invented a method for preparing a Zr-based metal-organic framework-based mixed matrix membrane (CN202311832921.X). First, formic acid was used as a regulator to prepare o-UiO-66 with a defective structure, and then trifluoromethylbenzoic acid was introduced through a ligand exchange strategy. The presence of the defective structure and the introduction of trifluoromethylbenzoic acid enhanced the diffusion rate and separation performance of the gas. However, it is still a challenge to prepare high-performance membrane materials with both permeability and selection through a one-step method.

[0004] Therefore, we proposed to use the principle that metal ions can coordinate with hydroxyl groups to form complexes, and use hydroxyl-rich functional small molecule β-cyclodextrin as a regulator. The coordination between hydroxyl groups and metal ions will occupy the original metal ion and ligand binding sites, and introduce ligand defects in MOFs through competitive coordination. The introduction of ligand defects will adjust the pore structure of MOFs on the one hand, and the hollow cylindrical structure of β-cyclodextrin itself provides additional channels for gas transport, thereby increasing the diffusion rate of gas molecules. In addition, the exposed metal sites and the presence of hydroxyl groups can also improve the adsorption capacity of CO2. Through multiple coupling effects, a membrane material with both high permeability and high selectivity is obtained. Summary of the invention

[0005] In view of the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a defective MOFs mixed matrix membrane for carbon capture. By utilizing the mechanism that metal ions can coordinate with hydroxyl groups to form a complex, the metal salt and the functional molecule are first pretreated to allow the two to fully contact to achieve the purpose of preferential coordination between the two, and then occupy the original binding sites by competitive coordination, introduce defective structures in MOFs, construct a low-resistance mass transfer channel for CO2, and improve the gas separation performance of the membrane material. The present invention adopts an in-situ synthesis method, utilizing the principle that the hydroxyl groups on the functional small molecules can coordinate with the metal ions, and introduces defect structures by means of competitive coordination. The introduction of defect structures, on the one hand, adjusts the pore structure of MOFs, increases its pore size and porosity, and on the other hand, the hollow cylindrical structure of the functional small molecules themselves not only provides an additional channel for gas transmission, further improving the permeability, but also the appropriate hollow pore size also improves the gas screening ability; on the other hand, the defect structure exposes abundant open metal sites in MOFs, and the interaction between the metal sites and CO2 enhances the gas adsorption performance; there is a hydrogen bond interaction between the unreacted carboxyl groups and the polymer matrix, which effectively improves the interface compatibility between the two; in addition, the hydroxyl groups also have a good affinity for CO2, and the multiple effects are coupled to obtain a membrane material with both high permeability and high selectivity.

[0006] The technical solution of the present invention:

[0007] A method for preparing a defective MOFs mixed matrix membrane for carbon capture, comprising the following steps:

[0008] (1) Regulation of defect structure

[0009] First, the metal salt and the functional small molecule are pretreated: the molar ratio of the metal salt to the functional small molecule is controlled to be 1:X, X=2-16, and the two are ground in a ball mill. The grinding process allows the two to fully contact so that they can coordinate to achieve the purpose of competitive coordination. The parameters are set to 30Hz, and the grinding time is 30min. After the grinding is completed, it is dissolved in a solvent and stirred at room temperature to completely dissolve it to obtain solution A; the molar ratio of the organic ligand to the metal salt is controlled to be 1:1, and then a certain amount of the organic ligand is dissolved in the solvent, and stirred at room temperature to completely dissolve it to obtain solution B; then the two solutions are mixed, stirred at room temperature for 30 minutes, and then ultrasonically treated. The mixture was evenly dispersed and bubbles were removed; the mixed solution was then transferred to a Teflon stainless steel autoclave. Due to the pretreatment of the metal salt and the functional small molecule, the two preferentially coordinated at high temperature, and then a defect structure could be introduced into the MOFs framework. MOFs were prepared by solvothermal method with a reaction time of 24 hours; after the reaction was completed, it was allowed to cool naturally and the mixture was collected by centrifugation; the obtained powder was washed three times by centrifugation with a solvent, and finally the product was placed in an appropriate amount of ethanol for activation, and centrifuged after standing for 3 days. The product was vacuum dried at high temperature overnight to ensure that the residual solvent in the MOFs pores was completely volatilized, and finally the activated defective MOFs were obtained for use;

[0010] (2) Preparation of gas separation membrane

[0011] First, the polymer particles and ethanol-water (mass ratio of 7:3) system were condensed, stirred and refluxed at 80°C to completely dissolve, thereby obtaining a transparent and uniform polymer solution with a mass fraction of 3%; then the prepared defective MOFs were dispersed in the polymer solution, and the addition amount of defective MOFs was controlled not to exceed 7% of the mass of the polymer particles. The resulting mixture solution was then dispersed and stirred at room temperature, and bubbles were removed by ultrasonic and standing treatment; finally, the mixture was spread on a polytetrafluoroethylene plate, and MMMs were obtained by solvent evaporation at 50°C.

[0012] (3) Gas separation performance test

[0013] Before the gas permeation test, the MMMs were placed in a vacuum chamber at 50 °C for 12 h to remove the residual solvent. The prepared membranes were then cut to a suitable size and adhered to a copper sheet. After standing for 6 h, the gas permeation and separation performance of the membranes were tested.

[0014] The MOFs is NH2-UiO-66.

[0015] The metal salt is ZrCl4, and the organic ligand is 2-aminoterephthalic acid.

[0016] The solvent thermal reaction temperature is 120°C.

[0017] The vacuum drying temperature is 100°C.

[0018] The solvent includes water, N,N-dimethylformamide (DMF) and ethanol.

[0019] The functional small molecule includes β-cyclodextrin.

[0020] The polymer particles include block polyetheramide resin (Pebax), self-polymerized microporous polymer (PIM-1) and the like.

[0021] Beneficial effects of the present invention: In view of the disadvantage that the current MOFs materials prepared by defect engineering cannot have both high permeability and high selectivity, the present invention proposes to utilize the mechanism of mutual coordination between metal ions and hydroxyl groups, use functional small molecules as regulators, and coordinate hydroxyl groups with metal ions to occupy the original binding sites, and introduce defect structures into MOFs in a competitive coordination manner. On the one hand, the introduced defect structures can effectively improve the pore environment of MOFs and increase their pore size and porosity. On the other hand, the hollow cylindrical structure of the functional small molecules themselves not only provides an additional channel for gas transmission, further improving the permeability performance, but also the appropriate hollow pore size also improves the gas screening ability. On the other hand, the defect structure exposes abundant metal sites in MOFs, and the metal sites have good interaction with CO2; there is hydrogen bond interaction between the exposed carboxyl groups and the polymer matrix, which effectively improves the interface descriptive properties; in addition, there is good affinity between hydroxyl groups and CO2, and under the coupling of multiple effects, the permeability and selectivity performance are improved together. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the XPS analysis diagram of NH2-UiO-66 and defective NH2-UiO-66 in the embodiment.

[0023] Figure 2 This is a graph showing the gas separation performance of the defective NH2-UiO-66 mixed matrix membrane when the loading amount is 5 wt.% in the example. DETAILED DESCRIPTION

[0024] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.

[0025] Embodiment 1:

[0026] Preparation of defective β-CD@NUiO: Defective β-CD@NUiO was prepared by solvothermal method. First, the metal salt and functional small molecule were pretreated. 0.233g ZrCl4 and 0.28375g β-cyclodextrin were placed in a grinder, and the parameters were set to 30Hz and ground for 30min. After the two were mixed evenly, they were added to 20ml DMF solution and stirred at room temperature for 10min to completely dissolve them. Then 0.181g 2-aminoterephthalic acid was slowly added to 30ml DMF solution, stirred at room temperature for 10 minutes, and after it was completely dissolved, the two solutions were mixed together and stirred for 30 minutes to mix them evenly, followed by ultrasonication for 5 minutes to remove bubbles, and then transferred to a 100mL Teflon stainless steel autoclave at room temperature, reacted at 120° for 24 hours by solvothermal method, and after it was naturally cooled, the obtained product was collected by centrifugation, and washed three times by centrifugation with water, DMF, and ethanol solvents respectively, and finally the product was placed in an appropriate amount of ethanol for activation, and centrifuged after standing for 3 days. The obtained product was vacuum dried at 100° for 12 hours to obtain the activated defective β-CD@NUiO. XPS analysis of the material shows that, Figure 1 As shown, the binding energy of Zr-O-Zr in the O 1s region diagram blue-shifts, indicating that some Zr-O-Zr bonds of defective β-CD@NUiO are broken during synthesis, and there are ligand defects. With the increase of the content of functional small molecules, the proportion of ligand deficiency also gradually increases;

[0027] Preparation of gas separation membrane: Pebax particles were mixed into ethanol-water (mass ratio of 7:3), condensed and stirred under reflux at 80°C to completely dissolve, thereby obtaining a transparent and uniform solution with a mass fraction of 3%; at the same time, a certain mass of defective β-CD@NUiO was dispersed into the casting solution to prepare MMMs with a filler loading of 5%, and the filler was fully dispersed by ultrasonication and stirring; the obtained mixture was stirred at room temperature for 5 hours, and the obtained mixture was ultrasonically treated for 3 minutes, and then allowed to stand for 2 minutes to remove bubbles; finally, the mixture was spread on a polytetrafluoroethylene plate, and MMMs were obtained by solvent evaporation at 50°C;

[0028] Gas separation performance test: The prepared MMMs were vacuum treated at 50 °C for 12 h to remove the residual solvent, and then the gas permeation and separation performance of the membranes were tested.

[0029] Embodiment 2:

[0030] Preparation of defective β-CD@NUiO: Defective β-CD@NUiO was prepared by solvothermal method. First, the metal salt and functional small molecule were pretreated. 0.233g ZrCl4 and 0.141875g β-cyclodextrin were placed in a grinder, and the parameters were set to 30Hz and ground for 30min. After the two were mixed evenly, they were added to 20ml DMF solution and stirred at room temperature for 10min to completely dissolve them. Then 0.181g 2-aminoterephthalic acid was slowly added to 30ml DMF solution, stirred at room temperature for 10 min, and after it was completely dissolved, the two solutions were mixed together and stirred for 30 min to mix them evenly, followed by ultrasonication for 5 min to remove bubbles, and then transferred to a 100 mL Teflon stainless steel autoclave at room temperature, reacted at 120° for 24 h by solvothermal method, and after it was naturally cooled, the obtained product was collected by centrifugation, and washed three times by centrifugation with water, DMF, and ethanol solvents respectively, and finally the product was placed in an appropriate amount of ethanol for activation, and centrifuged after standing for 3 days, and the obtained product was dried in vacuum at 100° for 12 h to obtain activated defective β-CD@NUiO.

[0031] Preparation of gas separation membrane: Pebax particles were mixed into ethanol-water (mass ratio of 7:3), condensed and stirred under reflux at 80°C to completely dissolve, thereby obtaining a transparent and uniform solution with a mass fraction of 3%; at the same time, a certain mass of defective β-CD@NUiO was dispersed into the casting solution to prepare MMMs with a filler loading of 5%, and the filler was fully dispersed by ultrasonication and stirring; the obtained mixture was stirred at room temperature for 5 hours, and the obtained mixture was ultrasonically treated for 3 minutes, and then allowed to stand for 2 minutes to remove bubbles; finally, the mixture was spread on a polytetrafluoroethylene plate, and MMMs were obtained by solvent evaporation at 50°C;

[0032] Gas separation performance test: The prepared MMMs were vacuum treated at 50 °C for 12 h to remove the residual solvent, and then the gas permeation and separation performance of the membranes were tested.

[0033] Embodiment 3:

[0034] Preparation of defective β-CD@NUiO: Defective β-CD@NUiO was prepared by solvothermal method. First, the metal salt and the functional small molecule were pretreated. 0.233g ZrCl4 and 0.5675g β-cyclodextrin were placed in a grinder, and the parameters were set to 30Hz and ground for 30min. After the two were mixed evenly, they were added to 20ml DMF solution and stirred at room temperature for 10min to completely dissolve them. Then 0.181g 2-aminoterephthalic acid was slowly added to 30ml DMF solution and stirred at room temperature for 10min. After it was completely dissolved, the two solutions were mixed together and stirred for 30min to mix evenly. Then, ultrasonication was performed for 5min to remove bubbles. Then, it was transferred to a 100mL Teflon stainless steel autoclave at room temperature and reacted at 120° for 24h by solvothermal method. After it was naturally cooled, the obtained product was collected by centrifugation and washed three times with water, DMF and ethanol solvents respectively. Finally, the product was placed in an appropriate amount of ethanol for activation, centrifuged after standing for 3 days, and the obtained product was vacuum dried at 100° for 12h to obtain activated defective β-CD@NUiO.

[0035] Preparation of gas separation membrane: Pebax particles were mixed into ethanol-water (mass ratio of 7:3), condensed and stirred under reflux at 80°C to completely dissolve, thereby obtaining a transparent and uniform solution with a mass fraction of 3%; at the same time, a certain mass of defective β-CD@NUiO was dispersed into the casting solution to prepare MMMs with a filler loading of 5%, and the filler was fully dispersed by ultrasonication and stirring; the obtained mixture was stirred at room temperature for 5 hours, and the obtained mixture was ultrasonically treated for 3 minutes, and then allowed to stand for 2 minutes to remove bubbles; finally, the mixture was spread on a polytetrafluoroethylene plate, and MMMs were obtained by solvent evaporation at 50°C;

[0036] Gas separation performance test: The prepared MMMs were vacuum treated at 50 °C for 12 h to remove the residual solvent, and then the gas permeation and separation performance of the membranes were tested.

[0037] Embodiment 4:

[0038] Preparation of defective β-CD@NUiO: Defective β-CD@NUiO was prepared by solvothermal method. First, the metal salt and the functional small molecule were pretreated. 0.233g ZrCl4 and 1.135g β-cyclodextrin were placed in a grinder, and the parameters were set to 30Hz and ground for 30min. After the two were mixed evenly, they were added to 20ml DMF solution and stirred at room temperature for 10min to completely dissolve them. Then 0.181g 2-aminoterephthalic acid was slowly added to 30ml DMF solution and stirred at room temperature for 10min. After it was completely dissolved, the two solutions were mixed together and stirred for 30min to mix them evenly. Then, ultrasonication was performed for 5min to remove bubbles. Then, it was transferred to a 100mL Teflon stainless steel autoclave at room temperature and reacted at 120° for 24h by solvothermal method. After it was cooled naturally, the obtained product was collected by centrifugation and washed three times with water, DMF and ethanol solvents respectively. Finally, the product was placed in an appropriate amount of ethanol for activation. After standing for 3 days, it was centrifuged and separated. The obtained product was vacuum dried at 100° for 12h to obtain activated defective β-CD@NUiO.

[0039] Preparation of gas separation membrane: Pebax particles were mixed into ethanol-water (mass ratio of 7:3), condensed and stirred under reflux at 80°C to completely dissolve, thereby obtaining a transparent and uniform solution with a mass fraction of 3%; at the same time, a certain mass of defective β-CD@NUiO was dispersed into the casting solution to prepare MMMs with a filler loading of 5%, and the filler was fully dispersed by ultrasonication and stirring; the obtained mixture was stirred at room temperature for 5 hours, and the obtained mixture was ultrasonically treated for 3 minutes, and then allowed to stand for 2 minutes to remove bubbles; finally, the mixture was spread on a polytetrafluoroethylene plate, and MMMs were obtained by solvent evaporation at 50°C;

[0040] Gas separation performance test: The prepared MMMs were vacuum treated at 50 °C for 12 h to remove the residual solvent, and then the gas permeation and separation performance of the membranes were tested.

[0041] Comparative Example 1:

[0042] Preparation of NH2-UiO-66: NH2-UiO-66 was prepared by solvothermal method. First, 0.233g ZrCl4 was added to 20ml DMF solution and stirred at room temperature for 10min to completely dissolve it; then 0.181g 2-aminoterephthalic acid was slowly added to 30ml DMF solution and stirred at room temperature for 10min. After it was completely dissolved, the two solutions were mixed together and stirred for 30min to mix them evenly, then ultrasonicated for 5min to remove bubbles, and then transferred to a 100mL Teflon stainless steel autoclave at room temperature, reacted at 120° for 24h by solvothermal method, and after it was naturally cooled, the obtained product was collected by centrifugation, and washed three times by centrifugation with water, DMF and ethanol solvents respectively, and finally the product was placed in an appropriate amount of ethanol for activation, and centrifuged after standing for 3 days, and the obtained product was vacuum dried at 100° for 12h to obtain activated NH2-UiO-66;

[0043] Preparation of gas separation membrane: Pebax particles were mixed into ethanol-water (mass ratio of 7:3), condensed and stirred under reflux at 80°C to completely dissolve, thereby obtaining a transparent and uniform solution with a mass fraction of 3%; at the same time, a certain mass of NH2-UiO-66 was dispersed in the casting solution to prepare MMMs with a filler loading of 5%, and the filler was fully dispersed by ultrasonication and stirring; the obtained mixture was stirred at room temperature for 5 hours, and the obtained mixture was ultrasonically treated for 3 minutes, and then allowed to stand for 2 minutes to remove bubbles; finally, the mixture was spread on a polytetrafluoroethylene plate, and MMMs were obtained by solvent evaporation at 50°C;

[0044] Gas separation performance test: The prepared MMMs were vacuum treated at 50 °C for 12 h to remove the residual solvent, and then the gas permeation and separation performance of the membranes were tested.

[0045] Comparative Example 2:

[0046] Preparation of defective TA@NUiO: Defective TA@NUiO was prepared by solvothermal method. First, 0.233g ZrCl4 and 0.4252g tannic acid were placed in a grinder, and the parameters were set to 30Hz and then ground for 30min. After the two were mixed evenly, they were added to 20ml DMF solution and stirred at room temperature for 10min to completely dissolve them. Then, 0.181g 2-aminoterephthalic acid was slowly added to 30ml DMF solution, stirred at room temperature for 10min, and after it was completely dissolved, the two solutions were mixed together and stirred for 30min to mix them evenly, and then ultrasonicated for 5min to remove bubbles, and then transferred to a 100mL Teflon stainless steel autoclave at room temperature, and reacted at 120° for 24h by a solvothermal method. After it was naturally cooled, the obtained product was centrifuged and collected, and washed three times with water, DMF, and ethanol solvents respectively. Finally, the product was placed in an appropriate amount of ethanol for activation, and centrifuged after standing for 3 days. The obtained product was vacuum dried at 100° for 12h to obtain activated defective TA@NUiO.

[0047] Preparation of gas separation membrane: Pebax particles were mixed into ethanol-water (mass ratio of 7:3), condensed and stirred under reflux at 80°C to completely dissolve, thereby obtaining a transparent and uniform solution with a mass fraction of 3%; at the same time, a certain mass of TA@NUiO was dispersed in the casting solution to prepare MMMs with a filler loading of 5%, and the filler was fully dispersed by ultrasonication and stirring; the obtained mixture was stirred at room temperature for 5 hours, and the obtained mixture was ultrasonically treated for 3 minutes, and then allowed to stand for 2 minutes to remove bubbles; finally, the mixture was spread on a polytetrafluoroethylene plate, and MMMs were obtained by solvent evaporation at 50°C;

[0048] Gas separation performance test: The prepared MMMs were vacuum treated at 50 °C for 12 h to remove the residual solvent, and then the gas permeation and separation performance of the membranes were tested.

[0049] At 0.3 bar and 25 °C, Figure 2As shown in the figure, compared with the unmodified NH2-UiO-66, the gas separation performance of the defective NH2-UiO-66 mixed matrix membrane is improved. This is because the introduction of functional small molecules introduces defect structures into the MOFs framework, adjusts the pore structure of the composite material, and thus improves the gas separation performance. This shows that it is feasible to prepare defective MOFs with hydroxyl-rich functional small molecules as regulators. Compared with tannic acid, the gas separation performance is improved more after the introduction of β-cyclodextrin. This is because β-cyclodextrin itself is not only rich in hydroxyl groups, but also has a hollow cylindrical structure, in which the hollow structure provides an additional transport channel for CO2 separation, and the appropriate pore size also makes it have better screening performance. Therefore, compared with tannic acid, using β-cyclodextrin as a regulator, its CO2 permeability is increased by 15.5%, CO2 / N2 selectivity is increased by 40%, and the performance is further improved. This shows that the preparation of defective MOFs for carbon capture using β-cyclodextrin as a regulator has good application prospects. In summary, defective MOFs have broad industrial application prospects in improving membrane permeability selectivity.

[0050] The above embodiments are the conception and description of the technical solution of the present invention, and are intended to allow more people familiar with this technology to understand the main content of the present invention and implement it, but the implementation of the present invention is not limited to the content of the above embodiments. Any modification, combination, simplification, etc. made without departing from the spirit and principle of the present invention shall be an equivalent replacement method and shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a defective MOFs mixed matrix membrane for carbon capture, characterized in that: Here are the steps: (1) Regulation of defect structure First, the metal salt and the functional small molecule are pretreated: the molar ratio of the metal salt to the functional small molecule is controlled to be 1:X, X=2-16; the two are ground, and after grinding, they are dissolved in a solvent, and stirred at room temperature to completely dissolve them to obtain solution A; the organic ligand is dissolved in a solvent, and stirred at room temperature to completely dissolve them to obtain solution B; then solution A and solution B are mixed, and the molar ratio of the organic ligand to the metal salt is controlled to be 1:1, and they are stirred at room temperature, and then ultrasonically treated to make them uniformly dispersed and remove bubbles; then the mixed solution is transferred to an autoclave, and MOFs are prepared by a solvothermal method, and the reaction time is 24h; after the reaction is completed, it is allowed to cool naturally, and the mixture is collected by centrifugation; the obtained powder is centrifuged and washed three times with a solvent, and finally the product is placed in ethanol for activation, and centrifuged after standing for 3 days, and the product is vacuum dried overnight at high temperature to ensure that the residual solvent in the MOFs pores is completely volatilized, and finally activated defective MOFs are obtained; (2) Preparation of gas separation membrane First, the polymer particles and an ethanol-water system with a mass ratio of 7:3 were condensed, stirred and refluxed at 80°C to completely dissolve, obtaining a transparent and uniform polymer solution with a mass fraction of 3%; then, the activated defective MOFs were dispersed into the polymer solution, and the amount of defective MOFs added was controlled not to exceed 7% of the mass of the polymer particles. The resulting mixture solution was then dispersed and stirred at room temperature, and bubbles were removed by ultrasonic and standing treatment; finally, the mixture was spread on a polytetrafluoroethylene plate, and MMMs were obtained by solvent evaporation at 50°C.

2. The preparation method according to claim 1, characterized in that: The MOFs is NH2-UiO-66.

3. The preparation method according to claim 1, characterized in that: The metal salt is ZrCl4.

4. The preparation method according to claim 1, characterized in that: The organic ligand is 2-aminoterephthalic acid.

5. The preparation method according to claim 1, characterized in that: The solvent thermal reaction temperature is 120°C.

6. The preparation method according to claim 1, characterized in that: The vacuum drying temperature is 100°C.

7. The preparation method according to claim 1, characterized in that: The solvent is water, N,N-dimethylformamide and ethanol.

8. The preparation method according to claim 1, characterized in that: The functional small molecule is beta-cyclodextrin.

9. The preparation method according to claim 1, characterized in that: The polymer particles are segmented polyether amide resin or self-polymerized microporous polymer.

10. The preparation method according to claim 1, characterized in that: The grinding is carried out in a grinder at 30 Hz for 30 min.

Citation Information

Patent Citations

  • Structural design and preparation method of separation composite membrane with ultrahigh carbon dioxide gas selectivity

    CN111111464A

  • Method and apparatus of managing decentralized storage for social medial based on block-chain

    KR1020250015349A

  • Rapid synthesis method for cyclodextrin-metal organic frameworks

    WO2017148439A1